RELATIONSHIP BETWEEN BLOOD GROUPS AND MALE INFERTILITY - Khan, Mohammad Shoaib; Ahmed, Zahoor; Hanif, Rohila; Zaman, Safeer; Ali, Irshad; Rahman, Jamil Ur; Zaman, Fasseh -uz- (Journal of Ayub Medical College Abbottabad, 2010)
Background: Blood is man's complete and unchangeable identity. The ABO and Rh groups are recognised as major and clinically significant blood groups. Blood group antigens are not only important in relation to blood transfusion and organ transplantation, but also have been utilised in genetic research, anthropology and tracing ancestral relation of humans. The objective the present study is to examine the blood group antigens in infertile men for assessing the relationship to male infertility and to know the frequency of various blood groups among infertile males in our population. Method: A total of 1,521 patients along with 460 proven fathers as controls were recruited for the present study from both rural and urban areas of Pakistan and referred to Department of Reproductive Physiology/Health, Public Health Divisions, NIH, Islamabad, during 2002 to 2006. Blood grouping (ABO) and Rhesus factors (Rh) was done by the antigen antibody agglutination test. Results: Overall distribution of blood groups in the studied population of 1,521 subjects was 35.50%, 28.27%, 26.89% and 9.34% for blood groups O, B, A and AB respectively. The ratio of control to patient was 1:3.3. Conclusions: The present preliminary study revealed that in our population the prevalence of male infertility in blood group O is invariably higher than in all other ABO blood groups, showing a strong relationship between blood group O and male infertility. Keywords: Blood groups, Male infertility, Pakistani population